Moderate Character Building Policy in Islamic Boarding Schools - Hambali, Muh.; Ulinnuha, Arna (Universitas Pendidikan Indonesia, 2023)
The purpose of this study is to discuss moderate characteristics in Anwarul Huda Islamic boarding school Malang. Characters have identification with students in everyday life. Character gives image implications to individuals and institutions. The aspect of Islamic boarding school institutions is not just building an image, but instilling moderate speech and behavior. A moderate civilization requires space for continuous habituation. This requires a specific strategy that has been used. This strategy is a coaching tool to foster moderate attitudes of students. The method in this study is classified as descriptive research. The data obtained by the researcher will be used in describing the implementation of the takzir method on the formation of moderate character of students using primary and secondary data sources. Data collection is carried out by observation, interviews and documentation The results of this study obtain a moderate character, namely national commitment is realized by commemorating Indonesian holidays, multicultural awareness by respecting each other's opinions when performing bahtsul masail, and non-violence, by not discriminating between senior and junior students supporting activities with roan (kerjabakti) and making articles and videos. The formation is influenced by the takzir method which includes four stages, the existence of rules, punishments, rewards, and consistency